TANGGUNG JAWAB PROVIDER DALAM HAL TERJADI KECELAKAAN YANG MENIMPA PELAKU OLAHRAGA KEDIRGANTARAAN MICROLIGHT/AUTOGYRO - Riela Pricilia, Nyoman; Rudy, Dewa Gde; Markeling, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014)
Aero sport has been a trending sport in Indonesia since January 17, 1972 when thissport has attracted people to established Federasi Aero Sport Indonesia (FASI) to held,guide, and leads other people who interested in aero sport there are still so manyquestions about the course of aero sport under FASI which is also including about theirresponsibility of damages, and losses for the athletes and/or the third party. This paperalso describes how FASI, as the provider will handle those damages and losses which ishappen to those athletes or third party by using empirical juridical approach and notethat the responsibility of the FASI against sports people is in terms of aerospaceguidance, supervision, and implementation as well as the loss of a third party FASItackle the problem of losses suffered by third parties to talk about it, weighed together,and declare whether the third party is eligible to get compensation.
Keywords: Responsibilities, Aero Sport, Accidents, FASI